Pengaruh Kualitas Layanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada Badan Penyelenggaraan Jaminan Sosial Ketenagakerjaan Gunungkidul - Pangesti, Ervina Ninda; Resmi, Siti; Utami, Alivia Meyrizka (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This research aims to examine the influence of service quality and customer satisfaction on customer loyalty of the Employment Social Security Administration (BPJS) in the Gunungkidul area. Apart from that, this research also examines how customer satisfaction is an intervening variable in the relationship between service quality and customer loyalty. The research sample was collected from 120 respondents who were BPJS Employment Gunungkidul participants who received services in the last 3 months (August-October 2023). Research testing uses regression with the Process Macro v4.3 bootstrapping method. The results are that service quality has a positive effect on customer loyalty and satisfaction, customer satisfaction also has a positive effect on customer loyalty, but customer satisfaction does not mediate the relationship between service quality and customer satisfaction. These results show how service quality and customer satisfaction can increase BPJS Employment customer loyalty. The research contributes to providing empirical evidence to be used as a reference for further research regarding service quality, customer satisfaction and customer loyalty and is expected to provide input, changes and improvements to the company as consideration in making decisions.